1997
DOI: 10.1074/jbc.272.11.7488
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous DNA Damage Stimulates Topoisomerase II-mediated DNA Cleavage

Abstract: Apurinic sites are position-specific poisons of topoisomerase II and stimulate DNA scission ϳ10 -18-fold when they are located within the 4-base overhang generated by enzyme-mediated cleavage (Kingma, P. S., and Osheroff, N. (1997) J. Biol. Chem. 272, 1148 -1155). To determine whether other major forms of spontaneous DNA damage also act as topoisomerase II poisons, the effects of position-specific apyrimidinic sites and deaminated cytosines (i.e. uracil:guanine mismatches) on the type II enzyme were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
70
1
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 52 publications
8
70
1
1
Order By: Relevance
“…Substitution of a ␤-hydroxyl for a hydrogen at the 2Ј-position of deoxycytosine (converting the deoxyribose ring to an arabinose) stimulated DNA scission mediated by the ␣ and ␤ isoforms of human topoisomerase II but did so with a positional specificity that differed from those of other DNA lesions. Moreover, in contrast to previous findings with abasic sites (26), additive or synergistic increases in DNA cleavage were observed in the presence of araC lesions and etoposide. These findings suggest sugar ring modifications can alter topoisomerase II function and raise the possibility that the enzyme may mediate some of the physiological effects of araC.…”
contrasting
confidence: 55%
“…Substitution of a ␤-hydroxyl for a hydrogen at the 2Ј-position of deoxycytosine (converting the deoxyribose ring to an arabinose) stimulated DNA scission mediated by the ␣ and ␤ isoforms of human topoisomerase II but did so with a positional specificity that differed from those of other DNA lesions. Moreover, in contrast to previous findings with abasic sites (26), additive or synergistic increases in DNA cleavage were observed in the presence of araC lesions and etoposide. These findings suggest sugar ring modifications can alter topoisomerase II function and raise the possibility that the enzyme may mediate some of the physiological effects of araC.…”
contrasting
confidence: 55%
“…AP sites are also formed by hydrolytic decay of DNA, which is estimated to produce around 10,000 AP sites per day in each mammalian cell (3). AP sites are cytotoxic (35,50), and as they lack genetic information, mutagenic (2,22,40).…”
Section: Discussionmentioning
confidence: 99%
“…These data also suggest that the induced ROS may act as signaling molecules rather than directly breaking the DNA duplex. Several previous studies have identified various mechanisms involved in the activation of Topo II-mediated DNA cleavage, including DNA structural modification, enzyme modification, acidic pH environment, and oxidative stress (Zechiedrich et al, 1989;Kingma and Osheroff, 1997;Li et al, 1999;Wang et al, 2001). The thiol-containing cysteine residue, generally as a catalytic element in the active domains of enzymatic proteins, can be oxidatively modified by ROS, thus leading to enzyme inactivation (Michiels et al, 2002).…”
Section: Discussionmentioning
confidence: 99%